Fortini, la memoria e il sacro: appunti per un confronto con Kafka - Palma, Massimo (L'ospite ingrato, 2025)
This article aims to reconstruct the ongoing, albeit sporadic, relationship between Franco Fortini and Franz Kafka. It focuses on the question of symbolism as the theoretical and expressive horizon that Fortini identifies in the Czech author. Starting with Fortini’s writings on Jonah in the immediate post-war period and analysing his contributions on Kafka, who began with the Paragraphs on Kafka in 1949, which emphasised the non-poetic nature of Kafka’s storytelling and its relationship to the sacred, this article concludes that Kafka is, according to Fortini, both a model of the political unconscious in Jameson’s sense and a paradigm of Fortini’s personal relationship with Judaism, as fully developed in Cani del Sinai. This work eventually identifies a problematic utopian dimension in Kafka’s approach to literature.